2019
DOI: 10.1111/ajco.13166
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of putting principles into practice: Resource tensions and real‐world constraints in multidisciplinary oncology team meetings

Abstract: The challenge of putting principles into practice: Resource tensions and real-world constraints in multidisciplinary oncology team meetings. AbstractMultidisciplinary oncology team meetings are crucial hubs for integrated, patient-centered diagnosis and treatment planning. Team meetings are designed to enact the best practice principles of multidisciplinary care. Yet surveys of clinicians and allied health providers who are members of multidisciplinary teams (MDTs) identify real-world constraints on putting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 48 publications
2
52
0
1
Order By: Relevance
“…10,13 The benefits of professional networks are supported by the CFIR domain outer setting which emphasize the importance of organizations promoting networking and teambuilding since this positively influence implementation by individuals sharing information and visions. 18 Further, it has also been shown that competence -, and network development is particularly relevant for health professional in county hospitals or low volume centres, 8,19 which is supported by this study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…10,13 The benefits of professional networks are supported by the CFIR domain outer setting which emphasize the importance of organizations promoting networking and teambuilding since this positively influence implementation by individuals sharing information and visions. 18 Further, it has also been shown that competence -, and network development is particularly relevant for health professional in county hospitals or low volume centres, 8,19 which is supported by this study.…”
Section: Discussionsupporting
confidence: 80%
“…18 Therefore, promotional interventions can increase commitment and interactive participation. 19,20 Several respondents reported resource constrains and lack of designated time to prepare for and participate in national, virtual MDTMs. These factors are interrelated, and lack of designated time has also in earlier studies been pointed out as a determinant for MDTM attendance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDT organization and structure vary across settings with differences reported in a range of practices, including data management and support. A recent review of MDT resources and practice identified the importance of data collection to effective MDT practice, as well as barriers to successful collection . A recent multisite MDT survey that investigated practical aspects of team meetings identified a lack of timely access to data and irregular conduct of audits to inform practice .…”
Section: Introductionmentioning
confidence: 99%
“…In this edition, Lamprell et al. have explored the constraints associated with putting these principles into practice . Their summary of the literature provides a snapshot of the potential barriers experienced in the Australian health environment for MDTs.…”
mentioning
confidence: 99%